The national effects of subnational representation: Access to regional parliaments and national electoral performance - Dinas, E; Foos, F (NOW Publishing, 2017)
According to scholarly wisdom, party competition at the subnational level plays a negligible role in national elections. We provide theory and evidence that qualifies this view. Subnational elections determine entrance into subnational parliaments, which provides essential organizational resources: members and money. Since in most cases the same political actors compete at all levels of government, they can make use of these resources to improve their statusin national party competition. We test our argument exploiting two institutional features of the German multi-level electoral context: the discontinuities generated by the 5% electoral threshold in German state elections, and the occurance of German state elections at different times in the federal election cycle. We find that parties that marginally cross the threshold for state parliamentary representation gain more members, and eventually perform better in national elections, but only if the party has sufficient time to organize between the state and the federal election. Consistent with our organizational explanation, bottom-up effects are more pronounced where state parliamentary parties receive more financial resources. Alternative mechanisms are tested, and receive no empirical support.